Form Analysis Sebagai Metode Kritik Matan: Menakar Keakuratan Pemikiran Robert Marston Speight (1924-2011) - Arif Chasanul Muna (AL QUDS : Jurnal Studi Alquran dan Hadis, 2021)
Form Analysis as a Method of Matn Criticism: Scrutinizing the Accuracy of Robert Marston Speight's Thought (1924-2011)Together with sanad, matn is the main component in a hadith. Among the important discussions regarding matn is the existence of several matn which have different editorials while informing one incident. This problem is usually called the problem of matn with various versions (ta'addud al-riwāyāt; variant version). In the West, this problem has received the attention of many academics, among them Robert Marston Speight. He offers a form analysis method for studying and researching the problem of matn with various versions. This paper systematically describes how the Speight analysis method is, and how its position is in the study of hadith in the West. Critical analysis of the Speight method was also carried out by comparing it with the views of other academics and also the views of muhaddiṡūn. This paper uses a qualitative method in the form of a research library with a critical analysis model. This paper shows several conclusions: the method of analysis used by Speight, namely form analysis, is the development of the method of analysis of the matn which has been introduced, especially by Schacht with the purposes of dating tradition; many academics both in the West and the East doubted Speight's method of analysis and criticized its accuracy; and when compared to the muhaddiṡūn method, the Speight method contains several methodological flaws.